Immunomodulatory activity of an anti-HSV-1 synthetic stigmastane analog - Michelini, Flavia Mariana (2012)
Many viral infections are associated with the development of immunopathologies and autoimmune diseases, which are of difficult treatment and for which no vaccines are yet available. Obtaining compounds that conjugate both antiviral and immunomodulatory activities in the same molecule would be very useful for the prevention and/or treatment of these immunopathologies. The compound (22S,23S)-22,23-dihydroxystigmast-4-en-3-one (compound 1) displays anti-Herpes simplex virus type 1 activity in vitro and reduces the incidence of herpetic stromal keratitis (HSK) in mice, a chronic inflammatory syndrome induced by ocular HSV-1 infection. In the present study, compound 1 showed opposite immunomodulatory properties in vitro. It induced the release of pro-inflammatory cytokines in HSV-1-infected epithelial cells of ocular origin, and significantly reduced the production of these cytokines in LPS-activated macrophages. RNA microarrays revealed various overexpressed and repressed genes in compound 1 treated infected epithelial cells and activated macrophages, many of which are associated with innate immune responses and inflammatory processes. These immunomodulatory properties of compound 1, together with its previously reported antiviral activity, make it a potential drug for the treatment of HSK and many other immunopathologies of viral and non-viral origin.